Safety of the standardized quality tree sublingual immunotherapy tablet: Pooled safety analysis of clinical trials. Issue 12 (15th May 2021) - Biedermann, Tilo; Couroux, Peter; Greve, Tina Maria; Mäkelä, Mika
Abstract: Background: The standardized quality (SQ) tree sublingual immunotherapy (SLIT)‐tablet has recently been approved for treatment of tree pollen allergy. Healthcare workers should be provided with detailed safety data for clinical use. Objective: To assess the tolerability and safety of the SQ tree SLIT‐tablet (12 SQ‐Bet) in adults and adolescents. Methods: Safety data were pooled from three double‐blinded, randomized, placebo‐controlled trials (2 phase‐II/1 phase‐III) including adults and adolescents 12–65 years with allergic rhinitis and/or conjunctivitis treated before and during one pollen season once‐daily with 12 SQ‐Bet ( n  = 471) or placebo ( n =  458): EudraCT no: 2012‐000031‐59; NCT02481856; EudraCT 2015‐004821‐15. Results: The most frequently reported investigational medicinal product (IMP)‐related AEs with 12 SQ‐Bet were oral pruritis (39% of subjects) and throat irritation (29%). IMP‐related AEs were mainly mild or moderate in severity, and the majority resolved without treatment and did not lead to treatment interruption/discontinuation. With 12 SQ‐Bet, oral pruritus was more frequent among subjects with pollen food syndrome (PFS) (45%) than without PFS (29%). The 12 SQ‐Bet did not seem to induce an increased risk of asthma: 7 events were reported in 7 subjects with 12 SQ‐Bet and 11 in 10 subjects with placebo. No differences were seen in the risk of moderate‐to‐severe IMP‐related AEs regardless of age, PFS status and asthma medical history. Conclusions: The 12 SQ tree SLIT‐tablet was well tolerated in tree pollen allergic subjects with no major safety concerns detected. This safety profile supports daily at‐home sublingual administration once the first dose is tolerated when administered under medical supervision. Abstract : Tolerability and safety of the SQ tree SLIT‐tablet was investigated using pooled safety data from two phase‐II and one phase‐III trials in adults and adolescents with allergic rhinitis and/or conjunctivitis. Most frequent treatment‐related adverse events with the tree SLIT‐tablet were oral pruritus and throat irritation. No differences were seen in the risk of moderate to severe adverse events across subgroups. Abbreviations: AEs, adverse.